Analysis of Factors Affecting Consumer Satisfaction (Case Study at Sherif Barbershop Lhokseumawe City) - Adnan, Adnan; Abubakar, Rusydi; Zulkarnaen, Teuku; Fhirasyan, Fharan (AIBPM Publisher, 2023)
The primary objective of this study is to assess and analyze the impact of customer value, store atmosphere, and social media marketing on Consumer Satisfaction at Sherif Barbershop in Lhokseumawe City. The research utilized associative methodologies and adopted random sampling to select participants, involving a total of 96 respondents. Primary data in this study were taken by interview and spreading questionnaires, and secondary data by journal and browsing to internet. Data analysis technique used is descriptive analysis method and multiple linear regression analysis, the classical assumption test, instrument test (validity and reliability), hypothesis testing, and the coefficient of determination by using SPSS version 27.0. The results of the F test indicate a statistically significant and valuable relationship between Consumer Satisfaction at Sherif Barbershop in Lhokseumawe City and the combined effects of customer value, store atmosphere, and social media marketing. Additionally, through individual assessments, it was found that each factor customer value, store atmosphere, and social media marketing exerted distinct yet substantial influences on Consumer Satisfaction at Sherif Barbershop in Lhokseumawe City.Â Â Keywords: Customer Value, Store Atmosphere, Social Media Marketing, Consumer Satisfaction